2003
DOI: 10.1111/1469-7610.00187
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antenatal anxiety and behavioural/emotional problems in children: a test of a programming hypothesis

Abstract: There is evidence that antenatal stress/anxiety has a programming effect on the fetus which lasts at least until middle childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
407
5
24

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 624 publications
(471 citation statements)
references
References 53 publications
25
407
5
24
Order By: Relevance
“…These studies controlled for a number of confounding variables including SES, maternal age, birth weight, gestational age, and biomedical risks during pregnancy. Similarly, children whose mothers experienced high levels of anxiety during pregnancy exhibited higher rates of behavioral and emotional problems at 47 and 81 months of age after controlling for obstetric risks, psychosocial disadvantage, and postnatal anxiety and depression (O'Connor et al, 2003). In the present study, the numbers of inhabitants in a household and household crowding represent crude and indirect indices of psychological stress.…”
Section: Discussionmentioning
confidence: 62%
“…These studies controlled for a number of confounding variables including SES, maternal age, birth weight, gestational age, and biomedical risks during pregnancy. Similarly, children whose mothers experienced high levels of anxiety during pregnancy exhibited higher rates of behavioral and emotional problems at 47 and 81 months of age after controlling for obstetric risks, psychosocial disadvantage, and postnatal anxiety and depression (O'Connor et al, 2003). In the present study, the numbers of inhabitants in a household and household crowding represent crude and indirect indices of psychological stress.…”
Section: Discussionmentioning
confidence: 62%
“…Although not as mechanistically revealing, the Avon Longitudinal Study of Parents and Children (ALSPAC, n = 14 551) initiated in the United Kingdom in 1999 has reported several sex differences with respect to maternal psychosocial distress (anxiety and perceived stress) during pregnancy effects on offspring behavior during infancy and childhood (prepubertal window), and at the age of 18 (Capron et al, 2015). Even when controlling for maternal postpartum affective state and obstetrical factors, maternal anxiety late in gestation was associated most robustly with hyperactivity/ inattentiveness in boys and total behavioral/emotional problems in boys and girls assessed at 4 years of age (O'Connor et al, 2003). Later in development, sex differences with respect to maternal antenatal anxiety and cortisol awakening response in a subgroup (n = 1000) of 15-year olds from this cohort were less prominent (O'Donnell et al, 2013).…”
Section: Knowledge Gained By Including Sabv In Studies Of Neurodevelomentioning
confidence: 99%
“…A wealth of studies have shown that offspring of mothers with high levels of psychosocial stress, depression or anxiety are at increased risk for adverse neurodevelopmental outcomes, showing more internalizing and externalizing behavior problems (O'Connor et al 2002;O'Connor et al 2003;O'Donnell et al 2014) higher symptoms of depression (Pawlby et al 2009;Pearson et at 2013;Plant et al 2013) and alterations in biological systems such as brain morphology (Buss et al 2010) and epigenetic profiles (Oberlander et al 2016). Higher levels of cortisol during pregnancy have also been related to offspring IQ (LeWinn et al 2009), behavior and temperament (de Weerth et al 2013).…”
Section: Introductionmentioning
confidence: 99%